Surgical management of tympanojugular paragangliomas with intradural extension, with a proposed revision of the fisch classification - Sivalingam, Shailendra; Konishi, Masaya; Seung-Ho, Shin; Raja Lope Ahmad, Raja Ahmad Al'konee; Piaza, Paolo; Sanna, Mario (Karger AG, Basel, 2012)
Background: Tympanojugular paragangliomas (TJPs) with intradural extension can be successfully treated by a single or staged procedure with low surgical morbidity. Objectives: To present the clinical findings and treatment methods used for surgically treating TJP with intradural extension, as well as to discuss the complications of treatment and the relative merits of single versus staged surgery by using a comprehensive literature review comparing objective outcome measures. Study Design: A retrospective case review of 45 cases of TJP with intradural extension. Setting: A quaternary skull base and neurotologic center. Materials and Methods: The charts of 45 patients with Fisch classification class C or D TJP with intradural extension, who were operated on from April 1988 to April 2010, were analyzed. Clinical findings and preoperative lower cranial nerve (LCN) palsy as well as postoperative totality of resection, postoperative LCN palsy and complications were studied. The types, indications, and distribution of staged procedures were also analyzed. Results: Out of 45 cases, 22 were C3di2. The IX and X cranial nerves were the commonest nerves affected preoperatively. Preoperative internal carotid artery management was performed in 16 cases. Twenty-nine cases had a single procedure and 16 had a staged procedure. The main indication for staged procedures was intradural extension of 2 cm or more. The infratemporal fossa approach (ITFA) type A was the main procedure in all cases. Overall, total resection was achieved in 68.8% of cases with postoperative cerebrospinal fluid leak in 4.4% cases. Postoperative House-Beckmann grade I–III facial nerve status was maintained in 80% of cases, and overall LCN preservation rate was 56.9%. There were no cases requiring tracheostomy, and 3 cases required delayed phonosurgical procedures to improve their voice. Conclusions: TJP with intradural extension can be successfully managed with the judicious use of staged procedures to reduce the incidence of postoperative cerebrospinal fluid leak. The ITFA did not cause an excessively high rate of facial nerve palsy, and the overall total resection and LCN preservation rate compares very favorably with previously published data.